(3GdedcjI GdacQjI (B:s (3GdJfhY GdHjhdhLj hGdJfejI GdeSJOGeI hMd GdeSGFd GdUYHI (B/s - (3ghQ, eGQJfs; (3HdjM, CMeO HOjYs; (3GdSjO, CMeO YHO GdNGdbs ((3GdQjGV(B: s (3OGQ GdeQjN ddfTQ(B, s, 2002)
(3NdajI GdfbGT GdOhdj, GdJQHS, Mbhb GdedcjI GdacQjI hGdeYQaI GdJbdjOjI, GdYdGbI Hjf GdJQHS hGJaGb GdJfhY GdHjhdhLj, GJaGb GdJQHS hMbhb GdedcjI GdacQjI, GdJQHS hfbd GdJcfhdhLjGs
Keywords: (3GdJfejI GdeSJOGeIs; (3GdedcjI GdYGeIs